2016
DOI: 10.3389/fnhum.2016.00642
|View full text |Cite
|
Sign up to set email alerts
|

Time to Move Again: Does the Bereitschaftspotential Covary with Demands on Internal Timing?

Abstract: When Bereitschaftspotentials (BPs) are measured, participants are required to voluntarily perform a predefined number of identical movements, with varying intervals between movements, exceeding some obligatory minimum interval. Participants might cope with these demands on timing by installing a slow, broadly tuned rhythm of activation, serving as an internal trigger for executing movements in time. The BP might reflect the rising phase of this activation, culminating at the movement. If so (i) not only should… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 59 publications
(85 reference statements)
2
15
1
Order By: Relevance
“…According to the proposed model, the iFg modulates excitatory influence of the pre‐SMA on the STN, and enhances the inhibitory output from the STN to M1. In addition, the BP amplitude observed in our study in the short‐ISI condition is comparable with the one observed in Verleger, Haake, et al (), wherein the minimum movement time was 1 s. In a speculative interpretation of these comparable amplitudes, the existence of a critical BP threshold during externally triggered response tasks might be proposed. This interpretation would also fit with the earlier onset of prestimulus components.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…According to the proposed model, the iFg modulates excitatory influence of the pre‐SMA on the STN, and enhances the inhibitory output from the STN to M1. In addition, the BP amplitude observed in our study in the short‐ISI condition is comparable with the one observed in Verleger, Haake, et al (), wherein the minimum movement time was 1 s. In a speculative interpretation of these comparable amplitudes, the existence of a critical BP threshold during externally triggered response tasks might be proposed. This interpretation would also fit with the earlier onset of prestimulus components.…”
Section: Discussionsupporting
confidence: 89%
“…Under the assumption that in the long-ISI condition no overlap should occur between the P3 relative to the preceding stimulus (s-1 P3) and the preparatory ERPs for successive trials (s), we hypothesize that the long-ISI condition should result in a substantially unaltered BP in the last 500 ms preceding stimulus onset. In addition, in agreement with the notion that BP onset is modulated by intermovement interval in self-paced movements (e.g., Verleger, Haake, Baur, & Śmigasiewicz, 2016), we expect an earlier BP onset in the long-ISI with respect to short-ISI condition.…”
Section: Introductionsupporting
confidence: 91%
See 3 more Smart Citations